Research Developments of Aerostatic Thrust Bearings: A Review - Qi Zhao; Mingchen Qiang; Yu Hou; Shuangtao Chen; Tianwei Lai (Applied Sciences, 2022)
In aerostatic thrust bearings (ATBs), a high-pressure gas film with a certain bearing capacity and stiffness is formed by passing high-pressure gas between the moving surface and the static surface. Aerostatic bearings have outstanding advantages in the following aspects: high precision, high speed, and long service life, etc. They are widely used in many fields, such as high-speed air spindles, precision machine tools, air-bearing guideways, turbine machinery, and high-speed drills. With the pursuit of higher efficiency and high-precision machining machinery, there is an increasing demand for high-performance ATBs. Much effort has been spent on the study of ATBs, such as improvements in load capacity and stiffness, and the enhancement of stability. Some significant progress has been achieved. In this paper, the research developments of ATBs are summarized from several aspects, such as theoretical models and experimental methods, static performance, dynamic performance, and applications. In addition, insights on the breakthrough and development trends of ATBs are put forward. It is hoped that this paper can provide some guidance for the design and application of ATBs.